Finite Element Analysis of Bone Stress for Miniscrew Implant Proximal to Root Under Occlusal Force and Implant Loading. Issue 7 (October 2015) - Shan, Li-Hua; Guo, Na; Zhou, Guan-jun; Qie, Hui; Li, Chen-Xi; Lu, Lin
Abstract : Abstract: Because of the narrow interradicular spaces and varying oral anatomies of individual patients, there is a very high risk of root proximity during the mini implants inserting. The authors hypothesized that normal occlusal loading and implant loading affected the stability of miniscrew implants placed in proximity or contact with the adjacent root. The authors implemented finite element analysis (FEA) to examine the effectiveness of root proximity and root contact. Stress distribution in the bone was assessed at different degrees of root proximity by generating 4 finite element models: the implant touches the root surface, the implant was embedded in the periodontal membrane, the implant touches the periodontal surface, and the implant touches nothing. Finite element analysis was then carried out with simulations of 2 loading conditions for each model: condition A, involving only tooth loading and condition B, involving both tooth and implant loading. Under loading condition A, the maximum stress on the bone for the implant touching the root was the distinctly higher than that for the other models. For loading condition B, peak stress areas for the implant touching the root were the area around the neck of the mini implant and the point of the mini implant touches the root. The results of this study suggest that normal occlusal loading and implant loading contribute to the instability of the mini implant when the mini implant touches the root.